2020
DOI: 10.1128/jvi.01834-19
|View full text |Cite
|
Sign up to set email alerts
|

BK Polyomavirus Hijacks Extracellular Vesicles for En Bloc Transmission

Abstract: Most people are asymptomatic carriers of the BK polyomavirus (BKPyV), but the mechanisms of persistence and immune evasion remain poorly understood. Furthermore, BKPyV is responsible for nephropathies in kidney transplant recipients. Unfortunately, the sole therapeutic option is to modulate immunosuppression, which increases the risk of transplant rejection. Using iodixanol density gradients, we observed that Vero and renal proximal tubular epithelial infected cells release two populations of infectious partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
(56 reference statements)
4
37
0
Order By: Relevance
“…A seminal work on Hepatitis A virus revealed that virus particles are released both in enveloped and non-enveloped states, with the envelope protecting virus particles from neutralising antibodies [ 3 ]. More recently, it was reported that other non-enveloped lytic viruses, such as Coxsackievirus B [ 4 ], Hepatitis E virus [ 5 ], Poliovirus [ 6 , 7 ], Polyomavirus [ 8 , 9 ], Rotavirus and Norovirus [ 10 ], can also exit the cells as cloaked in extracellular vesicles (EV). Further, it was observed that EVs could contain multiple virus particles, allowing infection of a unique cell with many virus particles at a time [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A seminal work on Hepatitis A virus revealed that virus particles are released both in enveloped and non-enveloped states, with the envelope protecting virus particles from neutralising antibodies [ 3 ]. More recently, it was reported that other non-enveloped lytic viruses, such as Coxsackievirus B [ 4 ], Hepatitis E virus [ 5 ], Poliovirus [ 6 , 7 ], Polyomavirus [ 8 , 9 ], Rotavirus and Norovirus [ 10 ], can also exit the cells as cloaked in extracellular vesicles (EV). Further, it was observed that EVs could contain multiple virus particles, allowing infection of a unique cell with many virus particles at a time [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most individuals are asymptomatics carriers of BK polyomavirus (BKPyV), which is responsible for nephropathies in recipients of kidney transplants [ 136 ]. Handala et al confirmed, via electron microscopy, that a single EV originating from an infected cell could transport dozens of viral particles [ 136 ].…”
Section: Role Of Evs In the Pathogenesis Of Viral Infectionsmentioning
confidence: 99%
“…Most individuals are asymptomatics carriers of BK polyomavirus (BKPyV), which is responsible for nephropathies in recipients of kidney transplants [ 136 ]. Handala et al confirmed, via electron microscopy, that a single EV originating from an infected cell could transport dozens of viral particles [ 136 ]. Additionally, the EV-associated BKPyV employed a cellular entry pathway differring from that of a non-EV-associated virion, as the EV-associated viral particles did not attach to the cell via cell surface sialylated glycans nor were they able to agglutinate red blood cells [ 136 ].…”
Section: Role Of Evs In the Pathogenesis Of Viral Infectionsmentioning
confidence: 99%
See 2 more Smart Citations